10-Year Real-World Data on Acute Myeloid Leukemia: : The Paradigm of a Public Health Center in Brazil - Campos, Camilla; Orathes Ponte Silva, Alini Maria; Feistauer, Felipe; Teixeira da Silva, Lais; Favano, Thiago; Salvino, Marco Aurélio (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2024)
Introduction: Despite advances in Acute Myeloid Leukemia (AML) diagnosis and treatment, the outcomes in low- and middle-income countries (LMIC) are far apart from those in high-income countries (HIC). Objective: To describe the clinical features and outcomes of AML patients in Brazil's public health system, we conducted a retrospective analysis of all cases of non-promyelocytic AML diagnosed within 10 years (2007- 2017) in northeastern Brazil, Bahia. Methodology: We analyzed the real-life outcomes of 62 patients diagnosed with non-promyelocytic AML between 2007 and 2017 at a university hospital in Northeast Brazil. We classified patients using the European LeukemiaNet 2022 guideline into favorable (n=8), intermediate (n=18), and adverse risk (n=7) groups. Twenty-nine were not otherwise classified because no cytogenetic and/or molecular tests were available at diagnosis. Results: Allogeneic bone marrow transplant (alloBMT) was performed in 16 patients (37%). Median overall survival (mOS) was seven months. Among patients receiving alloBMT, mOS was 49 months, while for the chemotherapy group, it was six months (P = 0.003). For 10-year real-life data, we found complete remission of 53%, 5-year OS of 27%, and a mortality rate during induction therapy of 27%, inferior to HIC. Conclusion: Inferior outcomes found in LMIC result from a multifactorial scenario and an unmet need in the worldwide panorama of AML.